Key activity descriptors of nickel-iron oxygen evolution electrocatalysts in the presence of alkali metal cations - Görlin, Mikaela; Halldin Stenlid, Joakim; Koroidov, Sergey; Wang, Hsin-Yi; Börner, Mia; Shipilin, Mikhail; Kalinko, Aleksandr; Murzin, Vadim; Safonova, Olga V.; Nachtegaal, Maarten; Uheida, Abdusalam; Dutta, Joydeep; et al. (Nature communications, 2020)
Efficient oxygen evolution reaction (OER) electrocatalysts are pivotal for sustainable fuel production, where the Ni-Fe oxyhydroxide (OOH) is among the most active catalysts for alkaline OER. Electrolyte alkali metal cations have been shown to modify the activity and reaction intermediates, however, the exact mechanism is at question due to unexplained deviations from the cation size trend. Our X-ray absorption spectroelectrochemical results show that bigger cations shift the Ni 2+/(3+δ)+ redox peak and OER activity to lower potentials (however, with typical discrepancies), following the order CsOH > NaOH ≈ KOH > RbOH > LiOH. Here, we find that the OER activity follows the variations in electrolyte pH rather than a specific cation, which accounts for differences both in basicity of the alkali hydroxides and other contributing anomalies. Our density functional theory-derived reactivity descriptors confirm that cations impose negligible effect on the Lewis acidity of Ni, Fe, and O lattice sites, thus strengthening the conclusions of an indirect pH effect. It is commonly accepted that electrolyte alkali metal cations modify the catalytic activity for oxygen evolution reaction. Here the authors challenge this assumption, showing that the activity is actually affected by a change in the electrolyte pH rather than a specific alkali cation.